TRAJEKTORI PEMEROLEHAN FUNGSI SINTAKSIS ANAK USIA 3 TAHUN: STUDI LONGITUDINAL BERPERSPEKTIF GRAMATIKA FUNGSIONAL - Suci Amioza Putri; Nabila Desriza; Najla Nabila; Nayla Labibah; Nuri Rahma Dani; Wafi Yudini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to identify patterns of syntactic function acquisition in three-year-old native Indonesian speakers. The method applied is a longitudinal mixed-methods design for 31 days through natural observation with the technique of listening to talk. Data were validated qualitatively via triangulation with linguistic experts, then analyzed quantitatively (pattern frequency and Mean Length of Utterance) and qualitatively using Halliday's Functional Grammar framework and usage-based theory. The results show the dominance of S+P structures (31.9%) and S+P+O (28.1%) with an MLU value of 3.41 morphemes. Micro-genetic analysis reveals three transition phases: consolidation, expansion, and integration, which proves that syntactic development is dynamic, non-linear, and responsive to pragmatic contexts. The conclusion confirms that syntactic acquisition is an active construction that organically integrates semantic content, socio-pragmatic particles, and cognitive capacity. Implications of the findings include the development of contextual language development assessment instruments, evidence-based early intervention strategies, and the optimization of interactional scaffolding in early childhood education (PAUD) pedagogy. This study fills the empirical gap in Indonesian language syntax acquisition and strengthens the functional paradigm in developmental psycholinguistics.